Petrographical and Paleontological Characterizations of the Quaternary Calcarenites along the Coastline of NE-Libya - Ahmed M. Muftah (Scientific Journal of University of Benghazi, 2020)
Quaternary calcarenites deposits can be traced sporadically along the Mediterranean coastlines including Libya, Tunisia, Italy, Malta and Cyprus. Quaternary calcarenites are cropping out at local places in Al Jabal al Akhdar forming the coastal rocks, few hundred meters above sea level. This paper aimed to describe and classify the Quaternary (Pleistocene and Holocene) calcarenites of Al Jabal al Akhdar based on the depositional texture and the manifested sedimentary structures. Four rocky beach localities are subjected to sampling for this study namely, Garyounis, Al Haniyah, Al Hammamah and Susah. They are mainly composed of marine deposited at more or less various water depths. The concerned calcarenites displayed an alternating band of soft and hard white to creamy, planar to festoon trough large scale cross bedded with local occurrences of root casts and land snails. The bioclasts are represented by small benthic foraminifers of miliolids, rotalids and textularids as well as ostracodes, echinoderm remains, mollusks and calcareous red algae. The calcarenite in the studied localities showed wide range of facies distribution on both lateral and vertical sense in terms of biofacies and lithofacies, the calcarenite grains in Susah region is bounded by calcite bridges filled fractured. However, the calcarenite in Garyounis area is characterized by the presence of highly molluskan shells concentration such as Cardium, with intercalated marls and clays enriched with Ostrea.